SYSTEMATIZATION OF THE IATROGENIC PATHOLOGIES OF MAXILLARY SINUSES - Gulyuk, A.G.; Varzhapetіan, S.D.; Barannik, N.G. (World of Medicine and Biology, 2019)
The study was aimed at systematize the modern stomatogenic iatrogeny based on the analysis of literature data and own observations. The meaning of the word iatrogeny includes all the cases of postoperative conditions, new diseases after treatment, complications of illnesses in case of unsuccessful treatment or diagnosis, negative consequences of medical activity, cases of the patient’s recovery against medical intervention. Iatrogeny is a patient's condition in which the fact of the medical intervention influence on its development and formation, or its course, or its outcome (positive or negative) is established. Stomatogenic iatrogeny can manifest itself in the form of: iatrogenic recovery, iatrogenic complication of the underlying disease, iatrogenic harm caused to health, development of iatrogenic concomitant disease. Systematization of stomatological iatrogeny was established on examples of clinical cases.
Keywords: iatrogeny; dentogenic iatrogeny; iatrogenic maxillary sinusitis; systematization of iatrogeny